A Technique for Calculation of Shell Thicknesses for Core-Shell-Shell Nanoparticles from XPS Data - Cant, David J. H. (Surf Interface Anal, 2016)
This paper extends a straightforward technique for the calculation of shell thicknesses in core-shell nanoparticles to the case of core-shell-shell nanoparticles using X-ray Photoelectron Spectroscopy (XPS) data. This method can be applied by XPS analysts and does not require any numerical simulation or advanced knowledge, although iteration is required in the case where both shell thicknesses are unknown. The standard deviation in the calculated thicknesses vs simulated values is typically less than 10%, which is the uncertainty of the electron attenuation lengths used in XPS analysis.